Free riding and the inefficiency of the private production of pure public goods - Albert G. Schweinberger; Richard Cornes (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1993)
Free riding is explained in a model of voluntary production of public goods, in terms of the heterogeneity of households. To achieve this the traditional essentially Ricardian model of voluntary production of pure public goods is generalised to comprise any number of private and public goods, factors of production and households. The efficiency losses from the under-production of public goods are related to the efficiency losses from free riding and the scale of the economy. A condition for Pareto improving reallocations within the public goods sector in terms of the popularity of the various public goods is put forward.
Keywords: 330